Original paperWhitening efficacy of plant extracts including Hippophae rhamnoides and Cassia fistula extracts on the skin of Asian patients with melasma - Khan, Barkat Ali; Akhtar, Naveed; Hussain, Irshad; Abbas, Khwaja Asad; Rasul, Akhtar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: Melasma/hyperpigmentation and solar damage of the skin remains a difficult problem to treat. Various types of whitening agents are used to treat hyperpigmentation. A change has been observed recently to use plant extracts as skin whitening agents. Aim: To compare the effectiveness of emulsion formulations containing plant extracts that include catechins/polyphenols and placebo without plant extracts, on patients with melasma. Material and methods: Two groups of 25 patients each (aged 21–35 years), who reported to the outpatient department of BV Hospital and Personal clinic of a dermatologist, were included in the study. Volunteers applied the formulations with plant extracts and placebo to one side of the cheek. Prior to the study, signed consent was obtained from each patient. The tyrosinase inhibitory activity of the extracts and formulations was tested in vitro . The pigment density of patients was evaluated biometrologically using Mexameter ® and subjectively using a visual survey before and after treatment of 12 weeks. The approval of the Institutional Ethics Committee of Faculty of Pharmacy, the Islamia University of Bahawalpur was obtained before the study. One-way ANOVA and Kruskal-Wallis tests were used in the statistical analysis. Results: A significant decrease in the level of melanin was determined in all 50 patients who used a plant extract containing catechin (p ≤ 0.05). The difference between pre- and post-treatment levels of melanin was statistically significant (p = 0.05). Formulations prepared with plant extracts containing catechin were found effective on melasma, compared to the placebo . Conclusions: Formulations containing plant extracts that are not yet being used widespread commercially on melasma could be an effective alternative treatment of melasma.